Climate Change under the Context of Neoliberalism: A Critical Discourse Analysis of Political Leaders' Speeches on the Paris Agreement. Issue 1 (November 2020) - Lin, Yu-Chih
Abstract: The aims of the Paris Agreement are against the threat of climate change. On 1 st June 2017, American President Donald Trump made a speech show his stance on the Paris Agreement. On 4 th November, America officially announced the process of withdrawal from the agreement had begun. It raised attentions globally. Political leaders, such as German Chancellor Angela Merkel, Former- Australian Prime Minister Malcolm Turnbull, Former- British Prime Minister Theresa May, Chinese leader Xi Jinping and French President Emmanuel Macron responded to the actions of the withdrawal action of the United States. This research examines the political leaders' speeches to explore the embedded ideology and rationality towards the Paris Agreement under the context of neoliberalism.